Effects of the Environment on Developmental Plasticity and Infection Success of Schistosoma Parasites – An Epigenetic Perspective - Augusto, Ronaldo de Carvalho; Duval, David; Grunau, Christoph (Frontiers in Microbiology, 2019)
Evidence of how environmental cues affect the phenotype and compatibility between Schistosoma mansoni and their hosts come from studies in environmental parasitology, and research on host diet and on chemotherapeutic treatment. Schistosomes deal with a multitude of signals from the water environment and cues that come from their host, in particular those that serve to recognize and destroy them, i.e. the immune system. These interactions shape not only directly the parasite’s morphology, metabolism and behavior in short-term but also their infection success and development into different stage specific phenotypes later in their life, and potentially in subsequent generations by modifying the parasites inheritance system. Thus, environmental signals that come from control measures will influence on the life cycle. This is a challenge since it can lead to unexpected and undesired outcomes. It can also be an advantage since once we understand how environmental cues trigger phenotypes we might apply them to push the right environmental button and corner parasites the way we want them to be.